Activation of NF-κB signaling in tissue-resident memory T cells promotes recurrent psoriasis in mice - Lin, Yukang; Chen, Jiaying; Du, Han; Chen, Yuchao; Liu, Zhaolin; Li, Xuejia; Li, Yongdan; Qiu, Feifei; Wen, Lingling; Xu, Siyuan; Liu, Huazhen (Frontiers in Immunology, 2026)
BackgroundRecurrence triggered by immunological memory is a critical challenge in the treatment of psoriasis. Tissue-resident memory T (Trm) cells are the primary pacemakers in recurrent psoriasiform dermatitis following stimulation and infection by previous pathogens. However, the mechanisms underlying Trm cell activation remain unclear.MethodsIn this study, imiquimod-induced recurrent psoriatic mice were established to characterize the phenotypes of different Trm cell subsets. CD8+/CD4+ Tcm cell injection and NF-κB inhibitor or agonist treatment were then used to investigate the role and mechanisms of Trm cells in recurrent psoriasis. Finally, CD8+ T cells and keratinocyte co-culture systems were established to investigate the effects of activating NF-κB activation in Trm cells.ResultsMice displayed severe psoriatic dermatitis after repeated imiquimod treatment. The CD8+ Trm cells, but not CD4+ Trm cells, were elevated in the skin of recurrent psoriatic mice. Injection of CD8+ Tcm cells injection elicited more severe psoriatic symptoms than imiquimod treatment alone, indicating that CD8+ Trm cells are critical participants in psoriatic recurrence. Phosphorylation of NF-kB p65 (RELA), p-IKKa, p-RelB and NF-kB p100/p52 was enhanced in the skin of imiquimod-induced recurrent psoriatic mice. NF-κB inhibitor/agonist treatment significantly suppressed or restored the dermatitis severity and CD8+ Trm cell levels in recurrent psoriatic mice. Meanwhile, NF-κB inhibition also restored the expression of DLAT in Trm cells. Finally, NF-κB inhibitors directly suppressed Trm cell activation and inflammation of Trm cells in vitro.ConclusionTogether, these findings suggest that canonical and non-canonical NF-κB signaling directly activates Trm cell differentiation, inhibits cellular cuproptosis, and promotes recurrent psoriasis.